Determination of the pathogenicity of the variant UPM 1432/2019 IBDV in SPF chicken eggs and chicken fibroblast cell line - Mansour, Ali Youssif; Omar, Abdul Rahman; Bejo, Mohd Hair; Alitheen, Noorjahan Banu; Isa, Nurulfiza Mat (Universiti Putra Malaysia, 2025)
The infectious bursal disease virus (IBDV) is a nuisance to chicken productivity in the global poultry industry due to its high pathogenicity. In this study, the pathogenicity of the UPM 1432/2019 variant was evaluated using specific pathogen-free (SPF) chicken eggs and fibroblast cell lines. This viral strain was isolated from chickens displaying symptoms of watery diarrhoea and ruffled feathers. Following inoculation, the SPF chicken eggs, and cell lines were meticulously monitored for indicators of viral replication and the onset of cytopathic effects (CPE). The results showed that the virus could replicate in the SPF eggs and cell lines due to the presence of CPE in some cells. In addition, virus-induced weight loss in infected embryonated chicken eggs was evaluated. The UPM 1432/2019 and UPM 1219/2019 strains demonstrated similar mortality rates and CPE features. These findings indicate that the UPM 1432/2019 variant is pathogenic in SPF chicken eggs and fibroblast cell lines. Furthermore, the new UPM 1432/2019 variant caused IBD with pathogenic characteristics similar to the traditional UPM 1219/2019 variant. The emergence of the UPM 1432/2019 variant poses a risk to the economy and poultry production and is potentially resistant to the existing bursal disease vaccines. Consequently, the UPM 1432/2019 variant may significantly contribute to economic losses for chicken farm operators. Moreover, this study provides essential information on the potential virulence of the UPM 1432/2019 variant of IBDV and its potential impact on the poultry industry.